Pengaruh Pemberian Jus Triticum aestivum L. Terhadap Kadar Gula Darah Mus musculus L. Hiperglikemia - Elsa Yuniarti; Sari Ramadhani; Linda Rosalina (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aims to examine the effect of wheatgrass juice on the blood sugar levels of M. musculus L. hyperglycemia. This research is an experimental study using a completely randomized design. This study used 25 mice for 42 days in two control groups, namely negative and positive. The positive group was given glibenclamide after sucrose induction. There were three treatments in this study, namely P1 50%, P2 75%, and P3 100%, which were taken with wheat grass juice after sucrose induction. Check blood sugar levels using Easy Touch. The data was tested by ANOVA, followed by DMRT at the five percent level. The results showed that, at the end of the experiment, T. aestivum L. juice affected M. musculus L. blood sugar hyperglycemia. The most optimal use of T. aestivum L is P3 (100%). Keywords: Blood Sugar, Hyperglycemia, Wheat Grass Juice